Use of innovative information and communication technologies and modern multimedia means in the educational process - Гумен, Олена Миколаївна; Коломієць, Наталія Ярославівна (Technology audit and production reserves, 2014)
The article provides an overview of the theoretical and methodological foundations of information and communication technologies (ICT) in higher education institutions at the present stage; positives and problems of the use of ICT in education are marked; the technique of the use of public multimedia means in educational process in the transition period for implementation of distance education elements into educational processes under difficult economic conditions is considered. It was found that the use of e-learning saves the lecturer’s time to prepare for classes, class time, and effectively influences the performance of students while processing theoretical material, fulfilling practical tasks, self-control of knowledge, working with supplementary materials, contributes to achievement of significant results in studies.